- #1

- 415

- 0

[tex]P_r(x)=\frac{1-r^2}{1-2r\cos x +r^2}[/tex]

and

[tex]P_r(x)=\frac{1-r^2}{1-2r\cos x +r^2}=\sum_{n=-\infty}^{\infty}r{|n|}e^{inx}[/tex]

and

[tex]f(x)=\sum_{-\infty}^{\infty}c_ne^{inx}[/tex]

which is continues

i need to prove that:

[tex]f_r(x)=\frac{1}{2\pi}\int_{-\pi}^{\pi}p_r(t)dt=\sum_{n=1}^{\infty}c_nr^{|n|}e^{inx}[/tex]

the solution says to use the convolution property

[tex]c_n(f)=c_n[/tex]

[tex]c_n(P_r)=r^{|n|}[/tex]

[tex]c_n(f_r)=c_n r^{|n|}[/tex]

but i cant see how the multiplication of those coefficient gives me the

expression i needed to prove

?

i only got the right side not the left integral

??